EDUKASI PENGETAHUN DAN PELATIHAN BANTUAN HIDUP DASAR PADA PERAWAT DI RUANG RAWAT JALAN RS ASRI - Wirdan Fauzi Rahman; Serly, Serly (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Individuals and groups or the general public are also currently required to be able to provide immediate assistance when facing an emergency. In order to be able to provide assistance according to the procedure, it is necessary to provide debriefing on Basic Life Aid. Nurses at ASRI Hospital are nurses who have the potential to be given training. Armed with a team or group of KKR Cadres (Youth Health Cadres) have been formed but do not have the knowledge and need to be equipped with BHD. The purpose of this service is to improve the knowledge and technology of nurses at ASRI Hospital regarding basic Life Assistance in emergency cases. The method used is the method used is interactive lectures and questions and answers, pre-test, intervention and post-test methods. As a result of counseling and training there is an increase in knowledge about Basic Life Support and an increase in skills in providing BHD. It is necessary to carry out counseling and outreach on an ongoing basis from the school, especially in terms of Basic Life Assistance